2011
DOI: 10.1002/anie.201006163
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Enantioselective Zirconium Catalyst for Intramolecular Alkene Hydroamination: Significant Isotope Effects on Rate and Stereoselectivity

Abstract: Asymmetric olefin hydroamination/cyclization is a promising method for the synthesis of optically active cyclic amines.[1] To date, the most selective catalysts are C 2 -symmetric rare earth and zirconium complexes. [2,3] These C 2 -symmetric catalysts contrast with seminal C 1 -symmetric ansa-lanthanidocenes that epimerize under catalytic conditions.[4] Despite advances, current asymmetric hydroamination/cyclization catalysts are highly sensitive to substrate substitution patterns.Two distinct pathways have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 28 publications
(22 reference statements)
3
73
0
2
Order By: Relevance
“…In addition, Sadow and co-workers reported that zirconium [69] and yttrium [70] complexes coordinated by similar ligand frameworks catalyze hydroamination, and the mechanistic data in this study imply that these reactions occur through the same six-membered transition state as that proposed for reactions of the alkaline earth systems. Sub- sequently, Schafer and co-workers proposed a similar transition state for the hydroamination of primary and secondary aminoalkenes catalyzed by zirconium complexes ligated by a tethered bis(ureate).…”
Section: Catalytic Reactions Involving Insertions Into the Metal-nitrsupporting
confidence: 70%
“…In addition, Sadow and co-workers reported that zirconium [69] and yttrium [70] complexes coordinated by similar ligand frameworks catalyze hydroamination, and the mechanistic data in this study imply that these reactions occur through the same six-membered transition state as that proposed for reactions of the alkaline earth systems. Sub- sequently, Schafer and co-workers proposed a similar transition state for the hydroamination of primary and secondary aminoalkenes catalyzed by zirconium complexes ligated by a tethered bis(ureate).…”
Section: Catalytic Reactions Involving Insertions Into the Metal-nitrsupporting
confidence: 70%
“…Stoichiometric experiments also helped to clarify the preferred seven-coordinate environment of this sterically accessible precatalyst. A recently disclosed mechanistic proposal from Sadow and coworkers [63] showed that H (or D) transfer is required to assist with a turnover-limiting ring closure step (Scheme 15.11 and Scheme 15.12). This alternative mechanistic profile, called proton-assisted C-N bond formation, has been further investigated computationally, and important insights into this cooperative mechanistic profile have been obtained independently by Tobisch [36].…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…These previous reports illustrate the challenge of designing selective and well-defined asymmetric catalysts for this reaction. While most of these contributions have been reviewed recently [72], the most significant recent contribution is from the Sadow laboratories whereby a chiral zwitterionic Zr complex can achieve enantiomeric excesses up to 98%, the highest reported to date, and furthermore, enantiomeric excesses in the 90% range and above are achieved for most disubstituted substrates leading to pyrrolidine products (Table 15.10) [63]. Impressively, these results are attained in a timely manner (<8 h) at room temperature giving excellent yields.…”
Section: Catalysts For Asymmetric Alkene Hydroaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…For asymmetric hydroamination reactions, their main catalytic pathways can be attributed to a variety of metals [16], bases [17] and Bronsted acids [18]. Late transition metals (Ir, Pd, Au, Rh) are highly attractive and desirable for asymmetric hyroaminations due to higher functional group tolerance for both inert-and intramolecular variants, lowest air and moisture sensitivity and provide higher enantioselectivities [19].…”
Section: Introductionmentioning
confidence: 99%